SALSA: a novel flow cytometry assay to detect ascorbate at the single-cell level - Bella Lee; Wendy Wan-Ting Chou; Heng-Yi Chen; Dena Mossad; Michael Hsu; Bridget Bowman; Kartick Patra; Huan Zhang; Fang-Yun Lay; Frederick A. Villamena; Gang Xin; Richard S Bruno; et al. (Redox Biology)
Ascorbate (AA) is an essential antioxidant and enzymatic cofactor with emerging roles in epigenetic regulation, redox biology, and immune function. However, single-cell quantification of intracellular AA has remained technically challenging. Here, we present SALSA (Single-cell Ascorbate Level Sensing Assay), a novel flow cytometry-based method that enables sensitive, specific detection of intracellular AA at the single-cell level. Inspired by the mechanism of the in vitro AA assay, we identified 4,5-diaminofluorescein (DAF-2), a common nitric oxide (NO) probe, as a selective AA reporter. We showed that the chemical oxidation of AA into dehydroascorbic acid (DHA) facilitated its reaction with DAF-2 to form a highly fluorescent product. Surprisingly, the DAF-2-DHA adduct exhibits a red-shifted emission spectrum distinguishable from those of DAF-2 alone or its NO-reactive product. This spectral shift enables the differentiation of signals into two channels, SALSAVerde (green) and SALSARoja (red-orange), with SALSARoja offering superior sensitivity and minimal NO interference. SALSA is quantitative, with a strong linear correlation between signal intensity and intracellular AA concentration. Using SALSA and CRISPR, we identified SVCT2 as the major AA transporter in a human cell line model. Applying SALSA to immune profiling revealed previously unappreciated heterogeneity in AA levels across immune subsets and developmental stages. Together, these findings establish SALSA as a robust and accessible method for probing AA dynamics at single-cell resolution, with broad potential applications in redox biology, immunology, and metabolism.